A Theory of Conglomerate Mergers: Reply - Mueller, Dennis C. (Quarterly Journal of Economics, 1970)
Journal Article A Theory of Conglomerate Mergers: Reply Get access Dennis C. Mueller Dennis C. Mueller Cornell University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 84, Issue 4, November 1970, Pages 674–679, https://doi.org/10.2307/1880849 Published: 01 November 1970